Temporizador para tomadas de uso geral e específico em Instalações Elétricas direcionado aos consumidores da tarifa branca - Furini Júnior, Humberto Luiz (2019)
A home automation and internet of things (IoT) has basic concepts with the possibility of programming and use of equipment for the purpose of providing more comfort and accessibility to the user. This paper aims to save electricity, basic tariff linked to the National Electricity Agency, ANEEL and amounts charged according to the hours of use. The prototype of the visa project controls or executes access control via a remote control, which sends as information to these captures, which performs at cheaper energy tariff times, analyzed according to a distributor with distribution. For the development of this project, IBM platform services were used, which allow the communication between user and microcontroller, the latter being the equipment that drives machines using solid state relay performance, programmed through a web page. which can be accessed through cellular equipment, computer or any other platform that has internet access. Thus, the work visa offers a possibility to control energy consumption to the consumer and a consequent reduction in the tariff to be paid, combining energy saving and money saving, introducing the concept of smart home.